2022
DOI: 10.1200/jco.22.00644
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes and Genetic Predictors of Response to Metastasis-Directed Therapy Versus Observation in Oligometastatic Prostate Cancer: Analysis of STOMP and ORIOLE Trials

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co‐primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. The initial STOMP and ORIOLE trial reports suggested that metastasis-directed therapy (MDT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 15 publications
(25 reference statements)
1
38
0
Order By: Relevance
“…The benefit of MDT was maintained at longer follow-up with five-year data showing a 34% ADT-free survival for the MDT group vs. 8% for the surveillance group, as well as higher castrate-resistant prostate cancer (CRPC)-free survival (76% for MDT vs. 53% for surveillance). A combined analysis of STOMP and ORIOLE also showed that median PFS was prolonged with MDT, compared with observation [ 63 ].…”
Section: Psma Pet In the Setting Of Metachronous Oligometastatic Diseasementioning
confidence: 99%
“…The benefit of MDT was maintained at longer follow-up with five-year data showing a 34% ADT-free survival for the MDT group vs. 8% for the surveillance group, as well as higher castrate-resistant prostate cancer (CRPC)-free survival (76% for MDT vs. 53% for surveillance). A combined analysis of STOMP and ORIOLE also showed that median PFS was prolonged with MDT, compared with observation [ 63 ].…”
Section: Psma Pet In the Setting Of Metachronous Oligometastatic Diseasementioning
confidence: 99%
“… 113 Finally, the long-term results of these 2 studies confirmed the benefit of MDT in patients with oligorecurrent PC. 114 The results of MDT are therefore promising in order to postpone the start of a systemic therapy and consequently its side effects. However, it must be emphasized that the control arm of the 2 studies was represented by observation which does not represent the standard of care of patients with metastatic PC.…”
Section: Discussionmentioning
confidence: 99%
“…Also in prostate cancer, the STOMP trial demonstrated radiotherapy (RT) or surgery to oligometastases improved androgen-deprivation-therapy-free survival and the ORIOLE trial demonstrated SABR improved PFS in castration-sensitive oligometastatic prostate cancers [ 11 , 12 ]. Pooled analysis from these two latter trials found a PFS benefit with treatment compared to observation (11.9 months vs. 5.9 months) [ 18 ].…”
Section: Lesson #2: Most Rcts Indicate That There Is Benefit From Abl...mentioning
confidence: 99%